Time-restricted feeding’s effect on overweight and obese patients with chronic kidney disease stages 3-4: A prospective non-randomized control pilot study - Lao, Bei-ni; Luo, Jiang-hong; Xu, Xue-yi; Fu, Li-zhe; Tang, Fang; Ouyang, Wen-wei; Xu, Xin-zhu; Wei, Meng-ting; Xiao, Bing-jie; Chen, Lin-yi; Wu, Yi-fan; Liu, Xu-sheng (Frontiers in Endocrinology, 2023)
Background: Time-restricted feeding (TRF) has become a popular weight loss method in recent years. It is widely used in the nutritional treatment of normal obese people and obese people with chronic diseases such as diabetes mellitus and hypertension, and has shown many benefits. However, most TRF studies have excluded chronic kidney disease (CKD) patients, resulting in a lack of sufficient evidence-based practice for the efficacy and safety of TRF therapy for CKD. Therefore, we explore the efficacy and safety of TRF in overweight and obese patients with moderate-to-severe stage CKD through this pilot study, and observe patient compliance to assess the feasibility of the therapy. Methods: This is a prospective, non-randomized controlled short-term clinical trial. We recruited overweight and obese patients with CKD stages 3-4 from an outpatient clinic and assigned them to either a TRF group or a control diet (CD) group according to their preferences. Changes in renal function, other biochemical data, anthropometric parameters, gut microbiota, and adverse events were measured before the intervention and after 12 weeks. Results: The change in estimated glomerular filtration rate (eGFR) before and after intervention in the TRF group (Δ = 3.1±5.3 ml/min/1.73m2) showed significant improvement compared with the CD group (Δ = -0.8±4.4 ml/min/1.73m2). Furthermore, the TRF group had a significant decrease in uric acid (Δ = -70.8±124.2 μmol/L), but an increase in total protein (Δ = 1.7±2.5 g/L), while the changes were inconsistent for inflammatory factors. In addition, the TRF group showed a significant decrease in body weight (Δ = -2.8±2.9 kg) compared to the CD group, and body composition indicated the same decrease in body fat mass, fat free mass and body water. Additionally, TRF shifted the gut microbiota in a positive direction. Conclusion: Preliminary studies suggest that overweight and obese patients with moderate-to-severe CKD with weight loss needs, and who were under strict medical supervision by healthcare professionals, performed TRF with good compliance. They did so without apparent adverse events, and showed efficacy in protecting renal function. These results may be due to changes in body composition and alterations in gut microbiota.